Использование уравнения диффузии при решении задачи механического обезвоживания - Анциферов, А. В.; Богданов, А. А. (НТУ "ХПИ", 2008)
В статті розглядається математична модель процесу механічного обезводнення на основі рівняння дифузії. Розглянуті однорідне й неоднорідне рівняння дифузії. Приведено обґрунтування початкового та граничних умов і вид виразу для неоднорідного рівняння. Задача вирішується методом Фурье. Побудовані графічні залежності зміни вологості зразка з часом і по його довжині.

The mathematical model of mechanical dehydration process is examined in the article on the basis of diffusion equation. The homogeneous and the heterogeneous diffusion equation are considered. The grounding of initialand bordering conditions are given together with the view of heterogeneous equation. The problem is solved by Fourier method. The graphic dependences of sample humidity changing by time and its length are built.
Keywords: прессовое оборудование; брикетное производство; вакуум-фильты; пористые среды; поток влаги; метод Фурье